Vigan [videorecording] heirloom of the North - Trofeo, Dik. ([Quezon City] Philippine Information Agency)
Vigan is famous for its antique houses. It also shows the historical events, culture, traditions and industries of Vigan.
Keywords: Vigan (Ilocos Sur).; Geography; Philippine history